2020
DOI: 10.1108/ijrdm-12-2019-0406
|View full text |Cite
|
Sign up to set email alerts
|

Millennials' attitude toward chatbots: an experimental study in a social relationship perspective

Abstract: PurposeChatbots represent an innovative channel for retailers to meet young customers' needs anywhere and at any time. Being an emergent technology, however, it is important to investigate more thoroughly how users perceive it, and which are the variables that enhance a positive attitude towards this technology. On this premise, this study applies a social relationship perspective to the design of chatbots addressed to younger consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 74 publications
7
112
0
2
Order By: Relevance
“…There have been a few studies discussed about the use of chatbots in business (e.g. Belanché et al , 2019; Sotolongo and Copulsky, 2018; Vassinen, 2018; De Cicco et al , 2020). For example, Belanché et al (2019) discussed about AI on financial technology (FinTech) and identified key drivers of robo-advisor adoption among customers.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been a few studies discussed about the use of chatbots in business (e.g. Belanché et al , 2019; Sotolongo and Copulsky, 2018; Vassinen, 2018; De Cicco et al , 2020). For example, Belanché et al (2019) discussed about AI on financial technology (FinTech) and identified key drivers of robo-advisor adoption among customers.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In the past couple of years, chatbots have become so well integrated into the online customer experience that customers can hardly discern whether they are interacting with a chatbot or a human (An, 2018; Luo et al , 2019). The rapid evolution in artificial intelligence (AI) has redefined the customer experience and created huge opportunities for companies to interact with customers using chatbots (Sidaoui et al , 2020; Hollebeek et al , 2021; Kumar et al , 2019; De Cicco et al , 2020). E-commerce capabilities integrated within chatbots have become one of the fastest growing uses of AI, and an increasing number of businesses are now using AI chatbots (hereafter, “chatbots”) in customer interactions (Okuda and Shoda, 2018; An, 2018) and influencing the online customer experience (Sidaoui et al , 2020; Wirtz et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggested that millennials are the ones that definitely will give a chance to AI and chatbots. [15] 4. STUDY METHOD Today there are many no-code platforms that chatbot development makes an intuitive and easy task.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Совершенствование системы распознавания голоса с помощью ИИ привело к массовому распространению чат-ботов и они рассматриваются в качестве важного технологического тренда во все большем числе публикаций начиная с 2016 года. Активное распространение мессенджеров также дало толчок развитию чат-ботов на сайтах компаний [5].…”
Section: постановка задачиunclassified